Supply Chain Integration in Chinese Manufacturing Company --- Case Study of Shanghai_Volkswagen, Haier and Foxconn - WANDI, MIAO (2012)
Abstract Purpose – The purpose of this dissertation research is to explore how are Chinese manufacturing companies practice supply chain integration strategies; and subsequently, figure out what are the barriers Chinese manufacturing companies to execute supply chain integration? Design/methodology/approach – The research will be based on the case study of three Chines manufacturing companiess – Shanghai- Volkswagen, Haier Household Appliances, and Foxconn. It applies the qualitative research, use semi-structured interviews for primary data collection; and then compare and contrast with previous secondary data research to find out whether theoretical is same with practical. Findings – There are five key findings were identified in total. First of all, companies in this research rarely rely on local third party logistic companies; secondly, to facilitate the integration of relationships, the three selected companies has their different ways like centralized purchasing, centralized supplier district, supplier classification, technological dependence, as well as joint decision making. The third key finding is that an advance order system could facilitate both internal and external integrations; fourthly, there are some specific strategies to manage physical flow when concern about different product types such as “milk run” and “postponement”. Finally, for the barriers of supply chain integration, it has found that, both internal (lack of internal communication) and external factors (unbalanced infrastructure, lack of standardization, and the constraints from supplier side) have impact for the supply chain integration.Therefore the objective of the research was met. Originality/value – Little or no research has been made in the field of supply chain integration in China; therefore, the findings of SCI strategies could be used in other companies in China, especially for those companies in the same sector. Moreover, this dissertation not only identify the main barriers of SCI practice in Chinese manufacturing, but also have confirmed with the interviewed companies whether they have been limited by these barriers. Therefore, the results of this research are reliable and practical to use. Keywords — Supply chain, Integration, Manufacturing company, China.